2018
DOI: 10.5808/gi.2018.16.4.e21
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Understanding of Uterine Microbial Ecology Associated with Metritis in Dairy Cows

Abstract: Metritis, the inflammation of the uterus caused by polymicrobial infections, is a prevalent and costly disease to the dairy industry as it decreases milk yield, survival, and the welfare of dairy cows. Although affected cows are treated with broad-spectrum antibiotics such as ceftiofur, endometrial and ovarian function are not fully recovered, which results in subfertility and infertility. According to culture-dependent studies, uterine pathogens include Escherichia coli , Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 66 publications
(99 reference statements)
2
27
0
Order By: Relevance
“…Several reports have approached the isolation of bacteria colonizing the uterus in postpartum of metritic and healthy cows [25]; nerveless, to date, no scientific work had isolated and characterized native vaginal E. coli from RB cows, as performed in the present study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several reports have approached the isolation of bacteria colonizing the uterus in postpartum of metritic and healthy cows [25]; nerveless, to date, no scientific work had isolated and characterized native vaginal E. coli from RB cows, as performed in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to keep in mind that, while E. coli is recognized as a bovine metritic pathogen, this bacterium has also been recovered from the vagina of heifers from weaning to breeding; likewise, it was isolated from the postpartum uterus of cows that did not develop clinical disease [20][21][22]. Nevertheless, most non-culturable efforts to study vaginal and uterine microbial communities of cows had reported that E. coli has turned out to be very rare [23][24][25]; meaning that E. coli is in a low relative abundance in the reproductive tract. These contradictory results may be due to the diversity of E. coli strains and the existence of virulent clones [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next-generation sequencing has enabled several groups to investigate microbiome influences on disease development. Bovine microbial communities have been described across many anatomical sites [ 37 , 38 , 39 , 40 ], including the mammary gland [ 41 , 42 , 43 ] and the uterus [ 44 , 45 , 46 , 47 ]. The composition of the bovine microbiome can affect the health [ 48 , 49 , 50 ] and performance of animals [ 51 ].…”
Section: Immunocompetence Of High Genetic Merit Dairy Cattle and Dmentioning
confidence: 99%
“…Escherichia coli (E. coli) and Trueperella pyogenes are commonly isolated from the affected cows in the first week of postpartum (Kassé et al., 2016; Sheldon et al., 2009). Other microorganisms that belong to the phylum Bacteroidetes (like Bacteroides pyogenes, Prevotella melaninogenica and Porphyromonas levii ) or to genus Fusobacterium have also been implicated in the aetiology of metritis (Bicalho et al., 2017; Cunha et al., 2018; Jeon & Galvão, 2018). Lochia from cows with retained placenta and severe metritis contained increased amounts of lipopolysaccharides (LPS), known as endotoxins which originate from the outer membrane of Gram‐negative bacteria (Dohmen et al., 2000; Mateus et al., 2003).…”
Section: Introductionmentioning
confidence: 99%